2023
DOI: 10.1021/acs.jafc.2c08580
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Baicalein’s Effect on Chlorpyrifos-Induced Liver Injury in Carp: Involving Macrophage Polarization and Pyropto sis

Abstract: Chlorpyrifos (CPF) is widely used in agriculture, plants, and buildings to kill pests and worms. Excessive environmental residues of CPF will result in soil and ecological contamination and toxicity to animals and humans. Baicalein (Bai), derived from the root of natural Scutellaria baicalensis, is a potent anti-inflammatory, antioxidant, and antitumor agent. The objective of this paper is to investigate the molecular mechanism by which Bai prevents CPF-induced hepatotoxic injury. Carp were kept in water conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Recent studies have indicated that naturally occurring food compounds can regulate macrophage polarization, such as Laminaria japonica polysaccharide, scoparone, and baicalein. Naturally occurring food compounds have garnered extensive attention due to their good biocompatibility and low production cost, making them potential options for regulating macrophage polarization and associated diseases . Sulforaphene (SFE) is one of the major isothiocyanates derived from radish seeds possessing the advantages of being readily isolated in large quantities, high purity, and low cost. , Multiple studies have substantiated its pronounced inhibitory capabilities against various types of cancer cells. , Furthermore, SFE has displayed notable antibacterial properties against various bacterial strains, including oral pathogens. , In recent years, studies have also shed light on the anti-inflammatory properties of SFE, elucidating its inhibitory effects on colitis, adipogenesis, and Alzheimer’s disease. However, the impact of SFE on the polarization of macrophages and periodontitis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that naturally occurring food compounds can regulate macrophage polarization, such as Laminaria japonica polysaccharide, scoparone, and baicalein. Naturally occurring food compounds have garnered extensive attention due to their good biocompatibility and low production cost, making them potential options for regulating macrophage polarization and associated diseases . Sulforaphene (SFE) is one of the major isothiocyanates derived from radish seeds possessing the advantages of being readily isolated in large quantities, high purity, and low cost. , Multiple studies have substantiated its pronounced inhibitory capabilities against various types of cancer cells. , Furthermore, SFE has displayed notable antibacterial properties against various bacterial strains, including oral pathogens. , In recent years, studies have also shed light on the anti-inflammatory properties of SFE, elucidating its inhibitory effects on colitis, adipogenesis, and Alzheimer’s disease. However, the impact of SFE on the polarization of macrophages and periodontitis remains unknown.…”
Section: Introductionmentioning
confidence: 99%